Leadership Style: Analyzing the Influence of Transformational Leadership on Organizational Innovation - Jabbar, Basne Farooq (International Journal of Humanities and Education Development (IJHED), 2022)
Over the course of the last few decades, our understanding of what constitutes effective leadership has evolved to become ever more nuanced and intricate. It has been discovered that organizational innovation is influenced by a wide variety of different elements. It has been established that one of the most important aspects impacting organizational innovation is the leadership style. This study's primary objective is to analyze the relationship between the qualities of transformational leadership and organizational innovation in order to better understand the latter. The research was conducted with 71 participants in Erbil, including those from the top five private businesses in the city. The empirical quantitative approach was utilized by the researchers in order to conduct the analysis for the current study. According to the findings, the characteristic of idealized influence that had the greatest value was equal to 0.737 more than 0.01. This shows that there is a strong and positive link between idealized influence and organizational innovation